Development of Learning Video Media on Pattern Transfer Techniques to Fabric (TEKA) for Pattern-making Making Subjects - Asfia, Yunita; Yafie, Evania; Aini, Nurul; Krisnanda, Thiessa; Nasrillah, Yusrin (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study aims to develop and determine the feasibility of the TEKA (Technique for Transferring Patterns to Fabric) instructional video as a learning medium for the Pattern Making subject at SMK Negeri 7 Malang. The research employed a Research and Development (R&D) approach using the 4D development model (Define, Design, Develop, and Disseminate). The media was validated by subject matter experts and media experts and was tested on a limited scale involving 30 tenth-grade students from the Fashion Design and Production program at SMK Negeri 7 Malang. The validation results from subject matter experts showed an average score of 3.81, categorized as